EXTRACTION AND SPECIATION OF CHROMIUM(VI) AND CHROMIUM(III) AS ION-ASSOCIATION COMPLEXES OF TETRAMETHYLAMMONIUM-CHROMATE - Valencia Widiyaningrum Wandoyo; Mudasir Mudasir; Roto Roto (Indonesian Journal of Chemistry, 2006)
A specific, selective and simple method for speciation of chromium(VI) and chromium(III) has been developed. This method is based on the quantitative extraction of chromium(VI) and chromium(III) as an ion association of tetramethylammonium-chromate in methyl isobutyl ketone (MIBK), followed by back extraction and preconcentration with an acidic diphenylcarbazide (DPC) solution. Back extraction was applied to achieve further preconcentration by a final factor of 20. The chromium(VI)-DPC complex was determined by a UV-Visible spectrophotometer. The optimum conditions of this method are as follows, optimum wavelength at 545 nm, MIBK as organic solvent, 7.5 mL of nitric acid (65%) for each 100 mL sample, mole ratio of TMAC to Cr(VI) of 2x104:1, 5 min shaking time, mole ratio of DPC to chromium(VI) of 8:1, and immediate UV-Vis measurement after obtaining of back-extract. The calibration curve was linear in the concentration range 0.00-0.40 µg.mL-1 of chromium(VI) with a regression equation of Abs=0.0038+1.7427x, in which x was the chromium species concentration ( µg.mL-1). The correlation coefficient (r) for the curve was 0.9991 and the detection limit was found to be 0.946 µg.mL-1. The result of analysis and speciation of chromium in water samples from a river near a leather processing plant in Yogyakarta area showed that the total content of chromium was in the range of 0.04 - 0.05 µg.mL-1 consisting of 0.03 - 0.04 µg.mL-1 of chromium(VI) and 0.002 - 0.01 µg.mL-1 of chromium(III). This result indicates that the concentration of chromium in the river is still below the safety limit.